2018
DOI: 10.3390/jof4030084
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Specimen Imbalance of Mitochondrial Gene Copy Numbers Predicts Clustering of Pneumocystis jirovecii Isolates in Distinct Subgroups

Abstract: The molecular detection of Pneumocystis jirovecii is an important therapy-relevant tool in microbiological diagnostics. However, the quantification of this pathogen in the past has revealed discordant results depending on the target gene. As the clinical variety of P. jirovecii infections ranges between life-threatening infections and symptom-free colonization, the question arises if qPCRs are reliable tools for quantitative diagnostics of P. jirovecii. P. jirovecii positive BALs were quantitatively tested for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…SARS-CoV-2 was detected using the Altona-RT-PCR assay as described previously, [ 4 ] and P. jirovecii was also analyzed by existing and published protocols. [ 5 , 6 ]…”
Section: Methodsmentioning
confidence: 99%
“…SARS-CoV-2 was detected using the Altona-RT-PCR assay as described previously, [ 4 ] and P. jirovecii was also analyzed by existing and published protocols. [ 5 , 6 ]…”
Section: Methodsmentioning
confidence: 99%
“…Mycotic infections pose an increasing threat to public health for several reasons. Opportunistic infections such as Pneumocystis pneumonia (PCP), candidiasis, cryptococcosis and aspergillosis are becoming increasingly problematic as the number of people with weakened immune systems increases, particularly people with HIV/AIDS or cancer [4,5,6,7,8]. In 2017, 8% of the Namibian population was HIV positive [9], which is one of the highest infection rates in the world [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…A decreased frequency of DHPS mutations in other countries including Switzerland, Italy, and Portugal has also been observed [15,18,20,22,[55][56][57][58]. Recent studies of DHPS mutations in North and Central Europe have also shown a low prevalence of DHPS mutations related to the scarce use of sulfa drugs [21,[59][60][61][62][63]. Only one study from Denmark of patients with PcP from before 2000 reported a prevalence of DHPS mutants of 20.4% [64].…”
Section: Developed Countriesmentioning
confidence: 99%